What is success? Gaps and trade-offs in assessing the performance of traditional social forestry systems in Indonesia - Bong, Indah Waty; Moeliono, Moira; Wong, Grace Yee; Brockhaus, Maria (Forestry Faculty, Universitas Hasanuddin, 2019)
Despite the growing interest in social forestry (SF), how much do we understand the social, economic and environmental outcomes and the conditions that enable SF to perform? In this article, we use a content analysis of literature on existing traditional SF practiced throughout Indonesia. It examines the outcomes of these systems and the conditions that enabled or hindered these outcomes to understand possible causal relations and changing dynamics between these conditions and SF performance. We discuss the gaps in how SF is assessed and understood in the literature to understand the important aspects of traditional SF that are not captured or that are lost when the diverse traditional systems are converted into other land uses. It aims to understand the potential trade-offs in the State’s push for formalizing SF if these aspects continue to be ignored.